Muslims and Humour. Essays on Comedy, Joking, and Mirth in Contemporary Islamic Contexts - Wibisono, Rizky Bangun (Universitas Islam Internasional Indonesia, 2025)
In 2015, French satirical magazine Charlie Hebdo became a global symbol of free speech after a deadly attack on its office, following its publication of cartoons depicting the Prophet Muhammad. The Western world rallied around the slogan Je suis Charlie, hailing the magazine as a bastion of comedic defiance against religious extremism. But amid the outpouring of solidarity, a deeper question lingered: Was this truly about defending humor, or was it about reinforcing the idea that some cultures, some religions, are inherently hostile to satire? After all, outrage over religious mockery is hardly exclusive to Islam—Hindu nationalist groups have protested depictions of their gods, and conservative Christians have long decried irreverent portrayals of Jesus. Yet, in public discourse, Islam alone is framed as uniquely humorless, its followers unable—or unwilling—to take a joke.